Designing Low Frequency I.C Filter Using Pseudo Resistor for Biopotential Measurements - Neshatvar, Nazanin (2010)
A Master of Science Thesis in Electrical Engineering submitted by Nazanin Neshatvar entitled, "Designing Low Frequency I.C Filter Using Pseudo Resistor for Biopotential Measurements," submitted in December 2010. Available are both soft and hard copies of the thesis.